GFP-Tagged Protein Detection by Electron Microscopy Using a GBP-APEX Tool in Drosophila - Bernard, Fred; Jouette, Julie; Durieu, Catherine; Le Borgne, Rémi; Guichet, Antoine; Claret, Sandra (Frontiers in Cell and Developmental Biology, 2021)
In cell biology, detection of protein subcellular localizations is often achieved by optical microscopy techniques and more rarely by electron microscopy (EM) despite the greater resolution offered by EM. One of the possible reasons was that protein detection by EM required specific antibodies whereas this need could be circumvented by using fluorescently-tagged proteins in optical microscopy approaches. Recently, the description of a genetically encodable EM tag, the engineered ascorbate peroxidase (APEX), whose activity can be monitored by electron-dense DAB precipitates, has widened the possibilities of specific protein detection in EM. However, this technique still requires the generation of new molecular constructions. Thus, we decided to develop a versatile method that would take advantage of the numerous GFP-tagged proteins already existing and create a tool combining a nanobody anti-GFP (GBP) with APEX. This GBP-APEX tool allows a simple and efficient detection of any GFP fusion proteins without the needs of specific antibodies nor the generation of additional constructions. We have shown the feasibility and efficiency of this method to detect various proteins in Drosophila ovarian follicles such as nuclear proteins, proteins associated with endocytic vesicles, plasma membranes or nuclear envelopes. Lastly, we expressed this tool in Drosophila with the UAS/GAL4 system that enables spatiotemporal control of the protein detection.